Self‐poisoning with 60 tablets of Apixaban, a pharmacokinetics case report. Issue 1 (12th November 2018) - Franck, Bénédicte; Dulaurent, Sylvain; El Balkhi, Souleiman; Monchaud, Caroline; Picard, Nicolas; Couderc, Sylvain; Marquet, Pierre; Saint‐Marcoux, Franck; Woillard, Jean‐Baptiste
Abstract : A 67‐year‐old man was admitted to the emergency department about 5 h after deliberate self‐poisoning with 300 mg of Apixaban. The clinical examination did not show any organ dysfunctions or haemorrhagic signs, and the patient's life was not in danger. The first analysis, upon admission, showed a concentration of 2655 μg l −1 of Apixaban. The Cmax was observed 17 h after the intake (3654 μg l −1 ), about four times the classical Tmax value (median [range]: 4 h [2–4]). The Apixaban was then eliminated following a first order elimination with a calculated half‐life of 10.8 h. The anti‐Xa activity seems to be linearly related to concentration up to 4000 μg l −1 . This report suggests that the use of activated charcoal should be effective up to 17 h after a massive intake. Abstract :